Modified extraction and characterization of keratin from Indian goat hoof: A biocompatible biomaterial for tissue regenerative applications. Issue 184 (13th October 2017) - Kumar, S. Logesh; Anandhavelu, S.; Sivaraman, J.; Swathy, M.
ABSTRACT: The Goat Hoof Keratin (GHK) is a valuable biodegradable substance for making tissue regeneration. The protein substance from GHK powder is extracted in a clean form by using modified shindai solution technique. Electrophoreical analysis produces polypeptide chains of molecular weight of 40–45 kDa using SDS-PAGE method. FTIR spectra show the characteristic absorption band for α-helix and β-sheet peptide bonds. DSC analysis provides the GHK denaturation occurred at temperature ranging from 200–250°C and thermal degradation occurs at 211°C & 387°C using TGA. The biocompatibility of GHK examined using MTT (3(4, 5-dimethylthiazolyl-2)-2, 5-diphenyltetrazolium bromide) assay of fibroblast cells shows 91% cell viability.